REVEALING THE POTENTIAL OF INDONESIAN COFFEE: ANALYSIS OF COMPETITIVENESS IN THE INTERNATIONAL MARKET - Dewi, Ni Made Ayu Vionita; Susrusa, Ketut Budi; Arisena, Gede Mekse Korri; Nurfadillah, Suryani; Prayoga, Kadhung (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
This research aims to analyze the competitiveness, and the factors influencing competitiveness, and to determine the position of Indonesian coffee exports in the international market in 2001-2022. The coffee product analyzed used HS code 0901. This research employed three calculation methods: Revealed Comparative Advantage (RCA) to measure comparative advantage, the Error Correction Model (ECM) to identify the factors affecting competitiveness, and the Trade Specialization Index (TSI) to determine the position of Indonesian coffee exports. The RCA value of this study indicated that coffee commodities have a comparative advantage with a value >1. The Trade Specialization Index (TSI) value showed that Indonesian coffee commodities are in the maturation stage, with a value of 0.9 < TSI ≤ 1. The ECM analysis indicated that competitiveness factors, export value, export volume, and GDP have an impact on the competitiveness of Indonesian coffee in the international market.